FAKTOR-FAKTOR PENYEBAB KECEMASAN PASIEN PADA TINDAKAN PENCABUTAN GIGI DI KLINIK BEDAH MULUT RSGM PROF. SOEDOMO FKG UGM - , PUTRI LISTIANI; , drg. Poerwati Soetji Rahayoe, Sp.BM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Anxiety is a common condition whenever comes to a dentist. The anxiety level in tooth extraction is caused by multiple factors. The aims of this study was to observe the cause factors of anxiety in tooth extraction treatment, which were